The impact of corporate governance on executive compensation and pay-performance sensitivity - Wu, Yinan (2020)
Executives are responsible for the company's daily operation management and major strategy decisions, which is directly related to the company performance. In the situation of increasingly fierce competition, how to establish an effective compensation incentive system for executives and how to solve the principal-agent problem has become a matter of concern. In this context, this study examines the impact of corporate governance on executive compensation and the pay-performance sensitivity using a comprehensive sample from more than 1000 non-financial Chinese listed companies during the period 2017-2019. This study takes executive compensation as the dependent variable, and for the independent variables, ROA is selected as an indicator to measure company performance, and four corporate governance elements including ownership concentration, CEO duality, board size and board independence are selected from the aspects of ownership structure and board structure. In order to study the impact of corporate governance on pay-performance sensitivity, the cross multiplicative term of ROA and corporate governance variables is added into the original model. The empirical results show that there is a positive relationship between executive compensation and firm performance. CEO duality will positively affect executive compensation in Chinese listed companies, while ownership concentration, board size, and board independence have a negative impact on executive compensation. As for the pay-performance sensitivity, the results also show that CEO duality can weaken the pay-performance link, larger board are more likely to link executive compensation to firm performance, while ownership concentration and board independence have no significant moderating effect in Chinese listed companies. On the basis of these findings, this research puts forward some useful suggestions and made some contributions to enrich the relevant literature. Keywords: Executive Compensation, Corporate Governance, Pay-performance Sensitivity